INTER-BANK CALL MONEY MARKET TRANSACTION IN INDONESIA - Aries Haryadi; Sahabudin Sidiq (Economic Journal of Emerging Markets, 2013)
Abstract This study analyzes the effect of Indonesian Bank loan, the amount of demand deposits, and the Indonesia economic crisis in 1997 on the interbank call money market transactions in Indonesia using a multiple linear regression method. This study finds that the variables influencing the interbank call money market transactions are the interest rate of interbank call money market and the check money. Both variables have positive effect on the interbank money market transactions in Indonesia.